2017
DOI: 10.3389/fpubh.2017.00037
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Behavior Change Techniques to Elicit Adherence to Clinical Practice Guidelines

Abstract: IntroductionTwo 2-day continuing education seminars were developed to address the orthopedic physical therapy deficits in Guyana. Material was presented in a way to address all stages of behavior change.MethodsSurveys evaluating preseminar and postseminar knowledge was conducted. Chart reviews to establish adherence to clinical practice guidelines were performed.ResultsPreseminar surveys revealed minimal knowledge of clinical practice guidelines, which was consistent with preseminar chart review data. Postsemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In most studies in the medical field, personal use behavior is influenced by behavioral intention [ 25 , 45 ], and TRA theoretical models also highlight this relationship [ 26 ]. Moreover, other studies have shown strong correlations between attitudes and intentions [ 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…In most studies in the medical field, personal use behavior is influenced by behavioral intention [ 25 , 45 ], and TRA theoretical models also highlight this relationship [ 26 ]. Moreover, other studies have shown strong correlations between attitudes and intentions [ 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%